Effect of Ovariohysterectomy at the Time of Tumor Removal in Dogs with Mammary Carcinomas: A Randomized Controlled Trial. (21st December 2015) - Kristiansen, V.M.; Peña, L.; Díez Córdova, L.; Illera, J.C.; Skjerve, E.; Breen, A.M.; Cofone, M.A.; Langeland, M.; Teige, J.; Goldschmidt, M.; Sørenmo, K.U.
Abstract : Background: Ovarian hormones play crucial roles in mammary carcinogenesis. However, whether ovarian ablation by ovariohysterectomy (OHE) improves the prognosis in dogs with mammary carcinomas is unclear. Objectives: Determine if OHE at the time of mastectomy improves the prognosis in dogs with mammary carcinomas and evaluate if hormonal factors influence the effect of OHE. Animals: Sixty intact dogs with mammary carcinomas. Methods: Dogs were randomly assigned in a 1 : 1 ratio to undergo OHE (n = 31) or not (n = 29) at the time of tumor removal. Peri‐surgical serum estradiol (E2) and progesterone concentrations were measured, tumor diagnosis was confirmed histologically, and tumor estrogen and progesterone receptor status was immunohistochemically determined. The dogs were monitored for recurrence and metastases every 3‐4 months for at least 2 years. Uni‐ and multivariable survival analyses were performed with relapse and all‐cause death as endpoints in addition to univariable subgroup analyses. Results: Overall, OHE did not significantly decrease hazard of relapse (hazard ratio [HR], 0.64; P = .18) or all‐cause death (HR, 0.87; P = .64) in univariable analyses. In multivariable analysis OHE did not significantly influence the hazard of relapse (HR, 0.54; P = .12), but an interaction effect was identified between ER status and E2 ( P = .037). Subgroup analysis identified decreased hazard of relapse in the OHE group compared to the non‐OHE group in the subsets of dogs with increased E2 (HR, 0.22; P = .012) or grade 2 tumors (HR, 0.26; P = .02). Conclusion: Dogs with grade 2, ER‐positive tumors, or with increased peri‐surgical serum E2 concentration represent a subset of dogs with mammary carcinomas likely to benefit from OHE.